Strategic Information Management, 3rd Edition - Galliers, Robert; Leidner, Dorothy (Routledge, 2013)
'Strategic Information Management' has been completely up-dated to reflect the rapid changes in IT and the business environment since the publication of the second edition. Half of the readings in the book have been replaced to address current issues and the latest thinking in Information Management. It goes without saying that Information technology has had a major impact on individuals, organizations and society over the past 50 years or so. There are few organizations that can afford to ignore IT and few individuals who would prefer to be without it. As managerial tasks become more complex, so the nature of the required information systems (IS) changes - from structured, routine support to ad hoc, unstructured, complex enquiries at the highest levels of management. As with the first and second editions, this third edition of 'Strategic Information Management: Challenges and strategies in managing information systems' aims to present the many complex and inter-related issues associated with the management of information systems. The book provides a rich source of material reflecting recent thinking on the key issues facing executives in information systems management. It draws from a wide range of contemporary articles written by leading experts from North America and Europe. 'Strategic Information Management' is designed as a course text for MBA, Master's level students and senior undergraduate students taking courses in information management. It provides a wealth of information and references for researchers in addition.